ISLAMIC EDUCATIONAL VALUES IN THE KATOBA TRADITION: AN ISLAMIC INITIATION RITE FOR CHILDREN IN THE MUNA COMMUNITY - Devi, Nur Amelia; Darnawati; Isna (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
The Katoba tradition is an Islamic initiation rite that functions as a medium for value education within the Muna community. This study aims to analyze the ritual structure, symbolic meanings, and Islamic educational values transmitted through the Katoba tradition, while also examining challenges to its sustainability amid social change. The research employs a qualitative ethnographic approach, with data collected through participant observation, semi-structured interviews, and ritual documentation. Data analysis follows Miles and Huberman’s interactive model, supported by Van Gennep’s rites of passage theory, Turner’s concept of liminality, and Geertz’s symbolic anthropology. The findings show that Katoba conveys core Islamic values, including tawhid, the shahada, honesty, responsibility, birrul walidain, and moral discipline, which are instilled through symbolic practices and community-based learning. This tradition plays an important role in shaping children’s religious identity and strengthening social cohesion. However, modernization and the influence of digital media pose challenges to the continuity of Katoba, highlighting the need for adaptive efforts to preserve its fundamental values